Konsep akal Menurut Perspektif Alquran dan Para Filsuf - Firdaus M. Yunus; Syamsul Rijal; Taslim HM Yasin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
This study aims to examine the position of reason in the Quran and philosophers point of view. As a qualitative study, research uses data from reading material available in libraries. The materials obtained were analyzed systematically so that the data could be justified. Intellect has a function of thinking and a tool to examine everything that is needed by humans. Reason as a reflection of the human rational soul has special powers that are not possessed by plants and animals. Human reason not only has rational power, it also has elements of